Exon-intron structure and sequence variation of the calreticulin gene among Rhipicephalus sanguineus group ticks - Porretta, Daniele (Parasit Vectors, 2016)
BACKGROUND: Calreticulin proteins (CRTs) are important components of tick saliva, which is involved in the blood meal success, pathogen transmission and host allergic responses. The characterization of the genes encoding for salivary proteins, such as CRTs, is pivotal to understand the mechanisms of tick-host interaction during blood meal and to develop tick control strategies based on their inhibition. In hard ticks, crt genes were shown to have only one intron with conserved position among species. In this study we investigated the exon-intron structure and variation of the crt gene in Rhipicephalus spp. ticks in order to assess the crt exon-intron structure and the potential utility of crt gene as a molecular marker. METHODS: We sequenced the exon-intron region of crt gene in ticks belonging to so-called tropical and temperate lineages of Rhipicephalus sanguineus (sensu lato), Rhipicephalus sp. I, Rhipicephalus sp. III, Rhipicephalus sp. IV, R. guilhoni, R. muhsamae and R. turanicus. Genetic divergence and phylogenetic relationships between the sequences obtained were estimated. RESULTS: All individuals belonging to the tropical lineage of R. sanguineus (s.l.), R. guilhoni, R. muhsamae, R. turanicus, Rhipicephalus sp. III and Rhipicephalus sp. IV analysed showed crt intron-present alleles. However, both crt intron-present and intron-absent alleles were found in Rhipicephalus sp. I and the temperate lineage of R. sanguineus (s.l.), showing the occurrence of an intraspecific intron presence-absence polymorphism. Phylogenetic relationships among the crt intron-present sequences showed distinct lineages for all taxa, with the tropical and temperate lineages of R. sanguineus (s.l.) being more closely related to each other. CONCLUSIONS: We expanded previous studies about the characterization of crt gene in hard ticks. Our results highlighted a previously overlooked variation in the crt structure among Rhipicephalus spp., and among hard ticks in general. Notably, the intron presence/absence polymorphism observed herein can be a candidate study-system to investigate the early stages of intron gain/loss before fixation at species level and some debated questions about intron evolution. Finally, the sequence variation observed supports the suitability of the crt gene for molecular recognition of Rhipicephalus spp. and for phylogenetic studies in association with other markers. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13071-016-1909-3) contains supplementary material, which is available to authorized users.